2022
DOI: 10.3390/app12136466
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Distributed Energy Storage on Distribution and Transmission Networks’ Power Quality

Abstract: This study investigates the effect of distributed Energy Storage Systems (ESSs) on the power quality of distribution and transmission networks. More specifically, this project aims to assess the impact of distributed ESS integration on power quality improvement in certain network topologies compared to typical centralized ESS architecture. Furthermore, an assessment is made to see if the network topology in which an ESS position supports its ability to restore node voltage magnitude within acceptable ranges. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This technique rearranges the voltage phases to zero, when the waveform passes zero with an increasing edge, and it counts the voltage phase by accruing mode at every sample point. Using the method of detection which based on the specification above, the phases and magnitudes of voltage can be simply calculated, and the voltage sag can be precisely determined [124].…”
Section: Period Phase Methodsmentioning
confidence: 99%
“…This technique rearranges the voltage phases to zero, when the waveform passes zero with an increasing edge, and it counts the voltage phase by accruing mode at every sample point. Using the method of detection which based on the specification above, the phases and magnitudes of voltage can be simply calculated, and the voltage sag can be precisely determined [124].…”
Section: Period Phase Methodsmentioning
confidence: 99%
“…Ref. [41] covers some of these impacts on the electric power system, specifically distribution transformers and underground cables, while [42] examines power quality issues in the distribution system. The primary components of the distribution transformer are the terminals of the magnetic and electrical circuits, the bushings, the tank, the oil, the radiator, the conservator, and the breather.…”
Section: Common Transformer Failuresmentioning
confidence: 99%
“…O. B. Adewumi et al [17] represented the influence of distributed Energy Storage Systems on PQ in distribution and transmission networks is analyzed. M. I. Ahmed et al [18] suggested that the OSS of DG using stochastic radial basis function to minimize the cost.In [19] a comprehensive study in power systema and the possible PQ issues has been studied highlighting the importance of CPD in mitigation of these problems.…”
Section: Introductionmentioning
confidence: 99%